Pengaruh Akuntabilitas Alokasi Dana Desa Dan Kelembagaan Desa Terhadap Kinerja Keuangan Melalui Digitalisasi - Khusna, Lia Safarotul; Adiwijaya, Zainal Alim (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Good ADD management shows the success of an institution's financial performance. Accountability is a guideline needed to manage public affairs including Village Funds. Village officials who are not in their field manage the financial management of village fund allocation, which can impact financial performance. With the quantitative method, the sample used was a total sampling from BPD in the Wonosalam District of 200 respondents. Data collection techniques in this research include interviews, questionnaires, question grids, and library research with multiple linear regression analysis and moderated regression analysis (MRA). The research results show that accountability in village fund allocation hurts Kinerja Keuangan. Meanwhile, Village Institutions have a positive effect on Kinerja Keuangan. Moderated by Digitalisasi, accountability in village fund allocation positively affects Kinerja Keuangan. Meanwhile, Village Institutions harmed financial performance, moderated by Digitalization. Accountability for village fund allocation and Village institutions is one factor that influences the Kinerja Keuangan of villages in Wonosalam District. These two factors can be strengthened by Digitalisasi. With the Digitalization of the Accountability of Village Fund Allocation and Village Institutions, Financial Performance in Wonosalam District villages has experienced better improvement